Investigation of serum thyroid hormones, iodine and cobalt concentrations across common aquarium-housed elasmobranchs - Wheaton, Catharine J.; Sullivan, Kathleen E.; Bassiouny, Enass; Burns, Charlene M.; Smukall, Matthew J.; Hendon, Jill M.; Mylniczenko, Natalie D. (Frontiers in Veterinary Science, 2025)
IntroductionThyroid disease is an important condition to understand in elasmobranchs, with goiters being predominant. To identify dysfunction, measuring serum thyroid hormone levels is a standard of practice for diagnosing disease in most species. Although these levels have been reported in elasmobranch literature, the testing methodology is varied and values are not clinically useful for most aquarium species. In a group of aquarium-housed elasmobranchs, thyroid hormone levels had been persistently low or not detectable in otherwise healthy animals as well as animals with thyroid disease. The concern for reliability of these results to diagnose thyroid disease, prompted a shift to serum iodine levels as a proxy to determine thyroid health.MethodsThis study assesses thyroid hormone and iodine levels as compared to thyroid disease stage in elasmobranchs with and without dietary supplementation, to determine the efficacy of using these serum values to guide clinical decisions.ResultsSerum thyroid hormone results were lower than the readable range of the standard curve in both sharks and rays; thus reported values are usually extrapolated. Including additional standards down to the limit of sensitivity improved detection, however increasing the sample volume tested was determined to be the most important factor for obtaining measurable results in low-value thyroid hormone samples. Serum iodine levels are reported in three groups of southern stingrays (Hypanus americanus). Other elasmobranch species maintained in aquaria with and without thyroid disease were used for biological comparisons. Non-goiter, diseased animals reliably had elevated levels (over baseline) of thyroid hormones and iodine; in goiter cases, hormones were not useful. Additionally, it was found that cobalt levels were also elevated in some disease states and correlated positively with serum iodine levels.ConclusionCurrent available thyroid testing may not provide clinically useful values unless methodology is adjusted, or disease is severe. Serum iodine may be a useful marker to investigate thyroid health. Further, while thyroid disease may be identifiable with thyroid hormones, it is not straightforward or substantial enough alone for diagnosis.